Japanese Communication Skill Analysis Through Saiwa Activities - Wardhana, Chevy Kusumah; Oesman, Andy Moorad; Setiawati, Ai Sumirah; Ayuningrum, Ainia Febriani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Communication skills in students is one of the important assets to improving the soft skills of conveying messages to others. The things that support a student to convey messages well are the ability to understand information well, and the ability to convey the message back to other parties. This also applies when someone is studying a foreign language, especially Japanese. If we do not have good communication skills, the information will not be conveyed properly. This study aims to describe the Japanese language communication skills of students in the Japanese Language Education Study Program, Universitas Negeri Semarang. This communication capability is carried out in the form of Saiwa activities or retelling information or news that has been listened. The research methodology used is to use self-help activities or retelling the news that students have listened. To measure this ability is done by means of presentation tests and interview tests. Based on the results of the presentation capability assessment, it can be seen that The average value of the interview results for the samples "fair" category. The average value of the acquisition of the results retelling information on the entire sample is "more than enough" category.